Energy-resolved distribution of electron traps for O/S-doped carbon nitrides by reversed double-beam photoacoustic spectroscopy and the photocatalytic reduction of Cr(vi). Issue 26 (4th March 2020) - Chuaicham, Chitiphon; Karthikeyan, Sekar; Pawar, Radheshyam R.; Xiong, Yihuang; Dabo, Ismaila; Ohtani, Bunsho; Kim, Yoonyoung; Song, Jun Tae; Ishihara, Tatsumi; Sasaki, Keiko
Abstract : ERDT patterns with the CBB position of undoped and O/S-doped C3 N4 . Abstract : We report for the first time to our knowledge the identification of heteroatom-doped and undoped C3 N4 with the energy-resolved distribution of electron traps (ERDT) near the conduction band bottom position (CBB) using reversed double-beam photoacoustic spectroscopy. The ERDT/CBB pattern is used to classify the type of elemental doping in C3 N4, related to photocatalytic efficiency.